2012
DOI: 10.1016/j.neuron.2012.03.043
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin Ameliorates Age-Dependent Obesity Associated with Increased mTOR Signaling in Hypothalamic POMC Neurons

Abstract: Summary The prevalence of obesity in older people is the leading cause of metabolic syndromes. Central neurons serving as homeostatic sensors for bodyweight control include hypothalamic neurons that express pro-opiomelanocortin (POMC) or neuropeptide-Y (NPY) and agouti-related protein (AgRP). Here we report an age-dependent increase of mammalian target of rapamycin (mTOR) signaling in POMC neurons that elevates the ATP-sensitive potassium (KATP) channel activity cell-autonomously to silence POMC neurons. Syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
160
2
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(177 citation statements)
references
References 67 publications
11
160
2
4
Order By: Relevance
“…Consistently, overactivation of mTORC1 in hypothalamic neurons induces aging-associated feeding behavior and obesity (44,83). Mori et al (44) found that POMC neuron-specific deletion of the Tsc1 gene, a major negative regulator of mTORC1, leads to long-term elevation of mTORC1 signaling associated not only with cellular hypertrophy but also with reduced axonal projections to the hypothalamic PVN, which are linked with hyperphagic obesity.…”
Section: Mtorc1 Signaling In the Hypothalamusmentioning
confidence: 95%
“…Consistently, overactivation of mTORC1 in hypothalamic neurons induces aging-associated feeding behavior and obesity (44,83). Mori et al (44) found that POMC neuron-specific deletion of the Tsc1 gene, a major negative regulator of mTORC1, leads to long-term elevation of mTORC1 signaling associated not only with cellular hypertrophy but also with reduced axonal projections to the hypothalamic PVN, which are linked with hyperphagic obesity.…”
Section: Mtorc1 Signaling In the Hypothalamusmentioning
confidence: 95%
“…The question of what happens to mTORC1 signaling during normal aging has therefore received significant attention. As reported in Table 1, numerous studies have reported increased mTORC1 signaling with age in HSCs (hematopoietic stem cells), hypothalamic POMC neurons, and in the liver and lung of mice (Chen et al ., 2009; Sengupta et al ., 2010; Yang et al ., 2012; Leontieva et al ., 2014; Calhoun et al ., 2015). …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the combined systemic disruption of 4ebp1 and 4ebp2 in mice increases the animal's sensitivity to diet-induced obesity, due to increased adipogenesis, reduced lipolysis, and enhanced fatty acid reesterifi cation in the adipose tissue ( 19 ). While these studies provide genetic evidence indicating a positive role for mTORC1 signaling in adipogenesis, they may be confounded by systemic effects of the gene deletions, as mTORC1 is known to also function in the central nervous system to regulate energy balance (20)(21)(22). The adipose-specifi c knockout of raptor , resulting in reduced fat accumulation in mice ( 23 ), confi rms an autonomous, and indispensable, function of mTORC1 in adipogenesis.…”
Section: Discussionmentioning
confidence: 99%